First images from the PIONIER/VLTI optical interferometry imaging survey of Herbig Ae/Be stars. Issue Volume 8:Issue S299(2013) (6th January 2014) - Kluska, J.; Malbet, F.; Berger, J.-P.; Benisty, M.; Lazareff, B.; Le Bouquin, J.-B.; Baron, F.; Dominik, C.; Isella, A.; Juhasz, A.; Kraus, S.; Lachaume, R.; et al.
Abstract: The close environment of Herbig stars starts to be revealed step by step and it appears to be quite complex. Many physical phenomena interplay: the dust sublimation causing a puffed-up inner rim, a dusty halo, a dusty wind or an inner gaseous component. To investigate more deeply these regions, getting images at the first Astronomical Unit scale is necessary. This has become possible with near infrared instruments on the VLTI. We have developed a new imaging method adapted to young stellar objects where we process separately the stellar component from the rest of the image to reveal the environment by using the spectral differences between these two components. We present the result of this method on the first imaging survey of Herbig stars carried out by PIONIER on the VLTI.